DAMPAK KEBERAGAMAN DEMOGRAFIS TENAGA KERJA TERHADAP KINERJA KARYAWAN DI PT XYZ - Ramadhani, Raysha; Firmansyah, Yayan (Ultima Management : Jurnal Ilmu Manajemen, 2023)
Abstract-There are already many employees in Indonesia who support diversity in their companies, yet still many work environments in companies are homogeneous. Not much research has been conducted on the workforce demographic diversity in Indonesia and there have not been many studies on diversity in Indonesia that have explored many dimensions. This study aims to examine the effect of workforce demographic diversity on employee performance at PT XYZ. The dimensions used for workforce demographic diversity are age, gender, education, religion, and ethnic. This research was conducted using a quantitative method. The proportionate stratified random sampling technique was used to determine the sample in this study. The number of respondents used in the study amounted to 178 respondents. The data analysis technique used is simple regression analysis. In the research that has been done, the results show that demographic diversity affects the performance of employees at PT XYZ The results showed that the demographic diversity of the workforce had an effect of 29.5% on employee performance. The implication that can be used by companies based on the results of this study is to apply justice in every company activity and start applying an inclusive culture. Further research can explore more about types or dimensions of diversity. Keywords: Diversity; Demographic; Performance